1973
DOI: 10.1159/000245471
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Recording of the Ankle Jerk in Old Age

Abstract: The ankle jerk has been recorded electrically in 150 hospital inpatients over the age of 60. The lateral position was found to be most convenient for elderly people. Reinforcement did not increase the chances of obtaining a positive result. In females, the incidence of absent ankle jerks was found to rise steadily with advancing age, particularly after 70. In men, the peak decade was 70–79 years. The overall incidence of absent ankle jerks was 42% in women and 36% in men. Over the age of 80, 50% or more of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…The frequencies reported in studies carried out among selected subjects are higher and vary from 12 to 26% for the knee jerk and from 38 to 76% for the ankle jerk [2,3,6], but because of patient selec tion bias, rates of absent deep tendon re flexes are probably overestimated, a conclu sion supported by Kokmen et al [4] who found that in neurologically healthy people the ankle jerk was absent in only 9.8% of cases. The rise in frequency of absent deep tendon reflexes with age has frequently been reported in previous studies [1,5,10,33,34] and this was confirmed in the present survey with the exception of the older age group examined. A possible expla nation may be that these subjects were 'ex traordinarily healthy' and, therefore, held down the expected rise of the frequency of this sign.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The frequencies reported in studies carried out among selected subjects are higher and vary from 12 to 26% for the knee jerk and from 38 to 76% for the ankle jerk [2,3,6], but because of patient selec tion bias, rates of absent deep tendon re flexes are probably overestimated, a conclu sion supported by Kokmen et al [4] who found that in neurologically healthy people the ankle jerk was absent in only 9.8% of cases. The rise in frequency of absent deep tendon reflexes with age has frequently been reported in previous studies [1,5,10,33,34] and this was confirmed in the present survey with the exception of the older age group examined. A possible expla nation may be that these subjects were 'ex traordinarily healthy' and, therefore, held down the expected rise of the frequency of this sign.…”
Section: Discussionsupporting
confidence: 93%
“…The small sample size of our older age group may, however, constitute a bias in the interpretation of the finding. In our survey, in agreement with that of Bryndum and Marquardsen [35], we did not find a clear association between absent deep ten don reflexes and the presence of risk factors for peripheral neuropathy, but a quantita tive assessment of glycemia was not per formed in all subjects, and other studies have outlined that areflexia in the elderly may be caused by diabetes mellitus [1,7]. Larger case-control studies are required to investigate this question definitively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous reports of neurological examinations in older adults indicated that these patients usually exhibited a less vigorous tendon reflex than younger individuals. '.2 However, deVries et al 3 measured the Achilles tendon reflex and obtained no significant difference between the young and old groups. This report presents the first of a series of experiments designed to determine the quality of segmental reflex function in older adults.…”
mentioning
confidence: 97%